The Effect of Multifloral Honey Addition on The Physico-chemical and Sensory Evaluation of Marshmallow - Dedes Amertaningtyas; Shofiya Naifa Abidah; Zahra Diza Iqlima Didi Rosidi; Christbugi Welda Dellani; Aldyon Restu Azkarahman (JURNAL TRITON, 2026)
This study aimed to determine the effect of multifloral honey addition on the physicochemical and sensory evaluation of marshmallows. The research was conducted using a laboratory experiment with a Completely Randomized Design (CRD), if there are differences, the Duncan Multiple Range Test (DMRT) will be used. This study consisted of 4 treatments with 5 replications: without multifloral honey addition (M0), 15% multifloral honey concentration (M1), 30% multifloral honey concentration (M2), and 45% multifloral honey concentration (M3), calculated on a volume-to-volume basis (v/v) relative to the total gelatin used in the marshmallow formulation. The variables in this study included moisture content, water activity, chewiness, Lab* color, reducing sugar, ash content, antioxidant activity, and sensory evaluation. The result showed that multifloral honey addition had a highly significant effect (P<0.01) on moisture content, reducing sugar content, ash content, and antioxidant activity (IC50) of marshmallow, and had a significant effect (P<0.05) on the decrease of color sensory evaluation. Multifloral honey addition showed no significant effect (P>0.05) on water activity (Aw), chewiness (N), color Lab*, as well as sensory evaluation parameters (taste, aroma, texture, and overall acceptance). The average values of the moisture content of marshmallows ranged from 26.22–27.98%; Aw 0.703–0.733; chewiness 2.94–3.30 N; brightness level (L*) 92.81–93.65; redness (a*) -0.376 – (-0.568); yellowness (b*) 7.062– 8.016; reducing sugar content 8.99–20.95%; ash content 0.61–2.65%; antioxidant activity (IC50) 110.63–462.83µg/ml; sensory evaluation including taste 3.8–4.09; color 4.45–4.74; aroma 3.74–3.91; texture 3.54–3.91; and overall acceptance 3.83- 4.09. The formulation with 15% multifloral honey addition (M1) was indicated as the optimal treatment based on physicochemical and sensory evaluation.